2011
DOI: 10.3171/2011.6.jns101958
|View full text |Cite
|
Sign up to set email alerts
|

Management of large vestibular schwannoma. Part I. Planned subtotal resection followed by Gamma Knife surgery: radiological and clinical aspects

Abstract: Considering the good tumor growth control and facial nerve function preservation as well as the possibility of preserving serviceable hearing and the low number of complications, subtotal resection followed by GKS can be the treatment option of choice for large VSs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
93
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 69 publications
5
93
0
3
Order By: Relevance
“…4,14,16,22,32,45 In a recent publication, Yang et al concluded that if the patient is asymptomatic, the tumor is smaller than 10 cm 3 , and/or the Koos grade is less than 4, SRS could be the first choice of treatment more likely to lead to tumor regression. 45 A similar conclusion was presented by van de Langenberg et al 39 in the first part of a recent study: radiological growth control was achieved in nearly 90% of cases in both series. In his editorial, Kondziolka affirmed-in the absence of ataxia, disabling headache, hydrocephalus, or refractive fifth cranial nerve neuralgia-SRS is a practical option.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…4,14,16,22,32,45 In a recent publication, Yang et al concluded that if the patient is asymptomatic, the tumor is smaller than 10 cm 3 , and/or the Koos grade is less than 4, SRS could be the first choice of treatment more likely to lead to tumor regression. 45 A similar conclusion was presented by van de Langenberg et al 39 in the first part of a recent study: radiological growth control was achieved in nearly 90% of cases in both series. In his editorial, Kondziolka affirmed-in the absence of ataxia, disabling headache, hydrocephalus, or refractive fifth cranial nerve neuralgia-SRS is a practical option.…”
Section: Discussionsupporting
confidence: 67%
“…4,21,35,36 SRS is generally used to treat small-to medium-sized VSs but has also demonstrated satisfactory results with larger lesions as well. 20,30,31,[39][40][41]45 Nevertheless, the latter represent a challenge for both surgeons and radiosurgeons, because a direct correlation between tumor size and facial nerve damage does exist in the postoperative period. Furthermore, the current standard therapeutic dose (12-13 Gy) may be too high and not well tolerated by healthy surrounding nervous structures, with potential adverse radiation effects, without effecting rapid volume reduction.…”
mentioning
confidence: 99%
“…The debate continues over complete versus incomplete removal as the best management strategy for patients with VS. To date, there have only been a few studies involving a limited number of patients in which outcomes of subtotal removal followed by adjuvant radiosurgery in the treatment of large VS have been analyzed [11,12,13,14,15,16,17]. In the present study, we achieved a 100% tumor control rate, with 87% of our patients showing excellent facial nerve function in the follow-up.…”
Section: Discussionsupporting
confidence: 56%
“…There have been encouraging reports wherein large VSs have been managed by planned STR followed by SRS. 36 Preservation of facial nerve function is reportedly good following SRS. 36 Indications and protocols for SRS are still evolving, and more reports are likely to emerge in the future that will increase the role for SRS.…”
Section: Management Algorithmmentioning
confidence: 99%
“…36 Preservation of facial nerve function is reportedly good following SRS. 36 Indications and protocols for SRS are still evolving, and more reports are likely to emerge in the future that will increase the role for SRS. However, a drawback is that of malignant transformation after SRS and although this has not been proven in a large study, this could lie between 1 in 1000 and 3 in 200,000 treated patients.…”
Section: Management Algorithmmentioning
confidence: 99%